Stress interaction behaviour in Alveolar cortical bone fracture / Noor Alia Md Zain, Ruslizam Daud and Muhamad Safwan Muhamad Azmi - Md Zain, Noor Alia; Daud, Ruslizam; Muhamad Azmi, Muhamad Safwan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
Improving the mechanical integrity of the dental implantation through optimal stress distribution between the implant and the surrounding bone has reduced the risk of bone injury and implant loosening risk. Inversely, the clinical failure of implantation will result in the formation of microcracks in the alveolar bone. The uncertainty of stress interaction intensity between microcracks has been an unsolved issue regarding the load transfer between the implant and alveolar bone. This study investigates the magnitude of stress shielding and stress amplification to explain the behaviour of double edge (DE) microcracks that are identically formed due to various stability conditions of implantation under occlusal loading. A series of finite element modelling have been conducted to simulate the stress shielding and stress amplification behaviour based on the displacement extrapolation method (DEM) and contour integral analysis. The occlusal loading schemes are translated into Mode I, Mode II and Mixed-mode loading. The presented DE models have demonstrated the transition behaviour of DE parallel microcracks into a single edge (SE) crack basic behaviour, where the crack unification limit (CUL) and crack interaction limit (CIL) are identified at lower and a higher rates of a/W. The occlusal loading has shown significant influence on the intensity of stress shielding and stress amplification behaviour in a form of DE-SE microcracks interaction for Mode I and Mixed-mode occlusal loading.